Multifunctional Gold Nanostars for Cancer Theranostics - Liu, Yang (Springer Theses, Recognizing Outstanding Ph.D. Research, 2018)
This thesis presents the development of theranostic gold nanostars (GNS) for multimodality cancer imaging and therapy. Furthermore, it demonstrates that a novel two-pronged treatment, combining immune-checkpoint inhibition and GNS-mediated photothermal nanotherapy, can not only eradicate primary treated tumors but also trigger immune responses to treat distant untreated tumors in a mouse animal model. Cancer has become a significant threat to human health with more than eight million deaths each year, and novel methods for cancer management to improve patients' overall survival are urgently needed. The developed multifunctional GNS nanoprobe with tip-enhanced plasmonics in the near-infrared region can be combined with (1) surface-enhanced Raman spectroscopy (SERS), (2) two-photon photoluminescence (TPL), (3) X-ray computed tomography (CT), (4) magnetic resonance imaging (MRI), (5) positron emission tomography (PET), and (6) photothermal therapy (PTT) for cancer imaging and treatment. The ability of the GNS nanoprobe to detect submillimeter intracranial brain tumors was demonstrated using PET scan - a superior non-invasive imaging modality - in a mouse animal model. In addition, delayed rechallenge with repeated cancer cell injection in cured mice did not lead to new tumor formation, indicating generation of a memorized immune response to cancer. The biocompatible gold nanostars with superior capabilities for cancer imaging and treatment have great potential for translational medicine applications.